1978
DOI: 10.2136/sssaj1978.03615995004200010034x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Deep Weathering Profile on Granite in Peninsular Malaysia: III. Alteration of Feldspars

Abstract: Feldspar grains or their pseudomorphs from the different weathering zones are studied with the SEM. Weathering commences with dissolution to form voids in the grains. Close to the rock, the first product is allophanic material present as globules adhering to the voids in the grains. In the δ zone the product is halloysite with some amorphous silica spherules. The surface of the pseudomorph has a hummocky appearance suggesting an amorphous intermediary phase prior to halloysite formation. Kaolinite formation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 0 publications
1
29
1
1
Order By: Relevance
“…None of the tubular forms of halloysite observed during plagioclase alteration in volcanic materials (Kirkman, 1981;Eswaran, 1979;Eswaran and DeConinck, 1971;Parham, 1969) or granites (Eswaran and Wong Chaw Bin, 1978c) were observed in this study. XRD analysis of altered andesites gave no indication of the presence of 1:1 phyllosilicates (Figures 4a, 4b) in either the <10-/xm or clay fractions.…”
Section: Resultscontrasting
confidence: 52%
“…None of the tubular forms of halloysite observed during plagioclase alteration in volcanic materials (Kirkman, 1981;Eswaran, 1979;Eswaran and DeConinck, 1971;Parham, 1969) or granites (Eswaran and Wong Chaw Bin, 1978c) were observed in this study. XRD analysis of altered andesites gave no indication of the presence of 1:1 phyllosilicates (Figures 4a, 4b) in either the <10-/xm or clay fractions.…”
Section: Resultscontrasting
confidence: 52%
“…They found that the abundance of secondary minerals within the grains increased towards the surface of the soil although grains at different stages of alteration were present in each horizon. The mineralogy of these weathering products is similar to that of the altered biotite described by Eswaran and Heng (1976) and Eswaran and Bin (1978), but little information is available in the literature on the mechanism of these transformations.…”
Section: Introductionmentioning
confidence: 90%
“…Eswaran and co-workers (Eswaran and Heng, 1976;Eswaran and Bin, 1978) described pseudomorphs of biotite from tropical soils which consisted of mixtures of mixed-layer minerals, tubular halloysite, kaolinite, and goethite. In the present work, however, tubular halloysite was not found to be a weathering product of biotite despite its presence as the major weathering product of associated feldspars.…”
Section: Morphological Propertiesmentioning
confidence: 99%